DEVELOPMENT OF GRAMMATICAL THOUGHT IN POLAND AT THE END OF 15-th – MID 18-th CENTURY - Lazarovych, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the analysis of the grammar books in the Polish language in the historic aspect. In the second half of the 16th century there has begun the formation of the Polish literary language and until the middle of the 17th century there has been the time of the "golden age" of development of the Polish language. At that time there appeared the first grammar books in the Polish language that were aimed, on the one hand, at regularizing the grammar studies and, on the other hand, at studying the native language.